Corrosion resistance of Structural Steel using Waste Plastic Oil. Issue 1 (March 2021) - Nirmala, R.; Priyadharshini, B.; Manoj Kumaar, C.; Eshanthini, P
Abstract: The failure of reinforced concrete structures is due to various surface damage or structural damage. The common problem identified for the repair of concrete structures is mainly because of Corrosion. In order to prevent the steel from corrosion effect, the various methodologies are being adopted. Core-shell theory was used to protect the steel material from the effect of corrosion by the application of cobalt oxide with zinc oxide on silica and alumina layer. According to this theory, the formation of effective protective layer is made to behave an anticorrosive coating. The combined effect of core and shell compounds enhances the efficacy of properties as a film of coating material for the steel used in the construction industry. The present study is an attempt on coating the steel reinforcement used in the construction industry using plastic oil extracted from the waste plastic which possesses the property of adhesion and resistance against corrosion.